Optimization of heat conversion from candle flame into electrical energy using a thermoelectric generator - Irfan Isdhianto; Tri Widodo Besar Riyadi; Yuke Hary Laksono; Wigo Ardi Winarko (JTTM : Jurnal Terapan Teknik Mesin, 2025)
Indonesia is still heavily reliant on fossil fuels, which has become an obstacle to integrating renewable energy into the national energy supply. This dependency also slows down the achievement of the NDC target to reduce emissions by 26%. Meanwhile, renewable energy continues to grow rapidly worldwide, with consumption increasing by around 3% per year. The purpose of this study is to maximize the conversion of heat energy from candle flames into electrical energy using thermoelectric generators (TEG). TEG works by utilizing the temperature difference between the hot side and the cold side to generate electricity through the Seebeck effect. In this research, four TEG modules were installed on candles and arranged in series to test the effectiveness of two types of cooling systems: a heatsink with a fan and a heatsink with water. Data collection was carried out by measuring the temperature and the performance of the cooling systems in generating electricity, which was evaluated based on the voltage, current, and power produced during the candle-burning process. The results showed that the water-cooled heatsink produced higher voltage and power compared to the fan-cooled heatsink. However, the fan-cooled heatsink was more effective in maintaining a stable temperature difference between the hot and cold sides, making it more suitable for long-term use. This study highlights the significant potential of TEG as an environmentally friendly and cost-effective alternative energy solution, particularly in utilizing everyday waste heat